The Implications of Fund Supported Adjustment Programs for Poverty : Experiences in Selected Countries: Occa Paper 58. (Occasional Papers; Occasional Paper ;, 1988)
This paper presents a study that focuses on specific adjustment programs for limited periods and is aimed largely at analyzing the short-run implications of the policy measures. The longer run implications are also discussed whenever relevant, since much of the rationale for policies and many of the beneficial effects on the poor are likely to be realized over time. The study also notes any compensatory targeting measures oriented to the poor, together with their implications for the adjustment efforts and the political viability of the programs. These analyses may provide lessons for improving the design of future adjustment programs. The chapter also summarizes the sample countries and programs; and describes the methodology used in the study. The results of the study suggest that adjustment programs in general have important distributional implications. During the process of adjustment, it is inevitable that some social groups gain while others lose, particularly when adjustment is aimed at a shift in sectoral resource allocation.